Hubungan Pengetahuan Ibu, Karakteristik Ibu, Dukungan Keluarga, dan Persepsi Ibu terhadap Kelengkapan Imunisasi Dasar - Annisa Rahmatia Dewi; Mevita Ganista Wati; Nandieta Ratu Assyfa; Puspa Saresawati Rae (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The government's ongoing program includes 11 doses of the complete basic immunization, which is administered to infants between the ages of 0 and 11 months. In Sukajaya Village, Tasikmalaya City, in 2024, the purpose of this study was to investigate the connection between maternal knowledge, characteristics, family support, and perceptions of completeness of basic immunization. This study used a quantitative cross-sectional approach. The review populace comprised of moms of babies who were important for the IDL target bunch in 2023 in Sukajaya Town, Tasikmalaya City, and the example of 93 respondents was chosen through purposive testing. In Sukajaya Village, Tasikmalaya City, in 2024, no significant relationships were found between the completeness of basic immunization and maternal knowledge, maternal characteristics, or family support (p-value >0.05). However, there was a significant relationship between maternal perceptions and the completeness of basic immunization (p-value 0.05). Active counseling should be offered to mothers of young children in order to raise their awareness of the significance of getting their children all of their essential vaccines. In addition, the puskesmas ought to pay more attention to the recording of toddlers in order to guarantee that the target for basic immunization coverage is met.